Strategic Determinants of Transfer Pricing in Indonesian Non-Financial Firms (E-Jurnal Akuntansi, 2025)
This study examines the effects of intangible assets, tax minimization, capital intensity, and corporate governance on transfer pricing among non-financial companies in Indonesia. The data were analyzed in EViews 12 using a fixed-effects panel model. The final sample comprises 4,220 firm-year observations from 844 non-financial companies over the study period. The results show that intangible assets and capital intensity are positively and significantly associated with transfer pricing. In contrast, corporate governance is negatively and significantly associated with transfer pricing. Tax minimization, while positive, is not statistically significant. Overall, the findings suggest that firms’ asset structures and the effectiveness of corporate governance play a more influential role than tax-related motives in shaping transfer pricing practices in Indonesian non-financial companies.
Keywords: Transfer Pricing; Intangible Assets; Tax Minimization; Capital Intensity; Corporate Governance